Effective optimization of emitters and surface passivation for nanostructured silicon solar cells. Issue 106 (1st November 2016) - Li, Ping; Wei, Yi; Tan, Xin; Li, Xiaoxuan; Wang, Yuxuan; Zhao, Zengchao; Yuan, Ze; Liu, Aimin
Abstract : High efficiency black silicon solar cells achieved by optimization of emitter and surface passivation. Abstract : Using a black silicon surface is a promising way to minimize the optical loss of solar cells; however, the strength of low optical loss is partially diminished due to an increase in surface recombination of nanostructured silicon surfaces. In this paper, we study the recombination mechanism of nanostructured silicon surfaces. Experimental results show that the loss in efficiency of nanostructured silicon solar cells is greatly dominated by the increased surface recombination and Auger recombination. In order to suppress the carrier recombination through the nanostructured surfaces, we developed a technique to modify the surface morphology and the doping concentration of the emitter. By adopting an optimized SiO2 /SiN X passivation scheme, we obtained a compromise between low emitter recombination velocities and low reflectance. Remarkable gains of 3.7% on average efficiency, 34 mV on open circuit voltage, 3.65 mA cm −2 on short circuit current density, and 4.65% on FF were obtained, comparing with the black silicon solar cells fabricated by a standard industrial process. A best solar cell of 18.5% efficiency was achieved.